Comments on ''Macro-Level Activity Spaces" - Fotheringham, A. Stewart (Professional Geographer)
This article presents a commentary note on the previously published article, "Macro-Level Activity Spaces: Some Nationwide Visitation Patterns," by S.E. White. It is claimed that in this article, White employed a very simple, traditional gravity model to reach conclusions regarding the visitation patterns of other cities by the residents of six U.S. cities. The author of this article points few problems with White's methodology and conclusions. The first error pointed here is regarding White's claim some debate regarding the bias inherent in the parameter estimates of the gravity model. It is commented that White's analysis results from the calibration of a log-linear model. The author further pointed errors in maps of residuals that White reported.